PELATIHAN ILMU KOMPUTER SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL MASYARAKAT - Ismail, Ismail; Syamsul Rizal; Natasya Amelia Yosa (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of information technology requires the community to have adequate digital literacy. However, there are still many groups in society who do not have the basic skills to optimally utilize computer technology. This Community Service (PKM) activity aims to improve the digital literacy of the community through basic computer science training. The methods used include theoretical material delivery, hands-on practice, and participant mentoring. The results of the activity show an increase in participants' understanding and skills in using computers and basic applications, which are expected to support their daily activities and increase community productivity. This activity proves that computer science training can be an effective solution in improving the digital literacy of the community.